2014
DOI: 10.4103/0973-6247.126689
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and beliefs of young, college student blood donors about Human immunodeficiency virus

Abstract: Introduction:Young people, who tend to be healthy, idealistic, and motivated, are an excellent pool of potential voluntary unpaid blood donors. Recruiting and retaining young blood donors improves the long term safety and sufficiency of a country's blood supply. Knowledge, attitude, and beliefs about Human immunodeficiency virus (HIV) should play an important role in prevention of disease transmission.Materials and Methods:This study was a questionnaire based survey, conducted to explore the levels of knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…The present study highlights the fact that a KAP study can serve as an important source of information about misconceptions, as has been highlighted previously by Dubey et al who concluded from their study that a spectrum of myths and misperceptions could be identified with the help of their KAP study emphasising the need of education and that results from their study may contribute to the development of appropriate educational and training material 19 . Published literature revolving around the use of interventions for continuous performance improvement in transfusion practices have been shown to be effective in bringing about a change in practices.…”
Section: Discussionsupporting
confidence: 75%
“…The present study highlights the fact that a KAP study can serve as an important source of information about misconceptions, as has been highlighted previously by Dubey et al who concluded from their study that a spectrum of myths and misperceptions could be identified with the help of their KAP study emphasising the need of education and that results from their study may contribute to the development of appropriate educational and training material 19 . Published literature revolving around the use of interventions for continuous performance improvement in transfusion practices have been shown to be effective in bringing about a change in practices.…”
Section: Discussionsupporting
confidence: 75%
“…The sample sizes ranged from 36 23 to 132 678. 52 The primary target population across studies were students (n=19), 10 , 14 , 15 , 17 , 21 , 23 , 26 , 27 , 29 , 31 , 34 , 35 , 37 , 38 , 40 , 42 , 46 , 47 , 49 general population (n=9), 9 , 13 , 18 - 20 , 43 , 48 , 51 , 52 healthcare workers [HCWs] (n=5), 8 , 24 , 28 , 41 , 50 people living with HIV (PLWHIV) (n=4), 25 , 32 , 33 , 36 and female sex workers (FSWs) (n=3). 11 , 12 , 45 More details are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies showed that the sample represented the target population, 20 , 24 , 25 , 27 , 33 , 51 , 52 the participants have been recruited appropriately, 8 , 11 , 12 , 16 , 18 , 33 , 43 and calculated the sample size. 11 , 18 , 20 , 22 , 25 , 33 , 43 Twenty-five studies described their study settings, 9 , 11 , 12 , 19 , 21 - 25 , 27 , 29 , 31 , 33 - 37 , 39 , 42 , 47 - 50 , 53 , 54 Thirty-two studies conducted the data analysis sufficiently 8 , 9 , 13 - 22 , 24 - 28 , 31 - 37 , 39 , 41 - 43 , 48 - 51 and five studies used standard criteria to assess HIV/AIDS. 19 , 22 , 28 , 35 , 48 The majority of the included studies measured precisely, 8 , 12 , 13 , 20 - 29 , 31 - 52 , 54 14 studies used appropriate statistical analysis,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saudi Arabia, each hospital has developed its own blood bank centre, where the majority of donations come from replacement donors rather than volunteer donors and with offering incentives such as time off work, blood credit card if they require blood in future and award medals (Alam and Masalmeh Bel, 2004). Furthermore, sociodemographic and geographic factors have an influence on blood donation attitude (Dubey et al, 2014;Dubey et al, 2014). Likewise, the convenience and satisfaction associated with when and where the donor gives blood were found to be important factors for donating blood (Boulware et al, 2002).…”
Section: Introductionmentioning
confidence: 99%